Virginia Woolf and Vanessa Bell: Memoirs of Julian - S. P. Rosenbaum (Cahiers Victoriens et Edouardiens)
This article publishes and comments on the memoirs of Julian Bell that Virginia Woolf and Vanessa Bell wrote shortly after he was killed in the Spanish Civil War. All of Vanessa Bell’s memoir and more than half of Woolf’s are included for the first time. The unpublished parts of Virginia Woolf’s memoir display its narrative shape and the extent to which it is a family memoir that reflects her relationships with Vanessa, Julian, and his brother Quentin (who originally published only part of Virginia’s memoir in his biography). Woolf’s memoir also illuminates her early memoir-biography of Vanessa and her late ‘Sketch of the Past.’ Vanessa Bell’s brief memoir-notes of Julian were written in the anguished days following the shock of his death and reveal how mother and son were the most important loves of their lives.